The Diffusion of Innovation in the Use of The Electric Propulsion Engine "Manta One" by Fishermen at Kelan Beach. - Zatmika Loka, Ni Putu Elena; Nugroho, Wahyu Budi; Kamajaya, I Gede; Pramestisari, Nyoman Ayu Sukma (JURNAL ILMIAH SOSIOLOGI: SOROT; Vol 5 No 1 (2025): JISSOROT, 2025)
This study focuses on the diffusion of Manta One technology innovation by fishermen at Kelan Beach. The research aims to describe and analyze the process and steps of the Manta One technology diffusion at Kelan Beach. A descriptive-explanatory approach was used in this study. The theoretical framework chosen to analyze the diffusion is Everett M. Rogers' diffusion of innovations theory. The findings reveal that the diffusion of Manta One technology at Kelan Beach began in 2019. The motivation for upgrading from conventional to electric engines stems from Azura Indonesia's desire to support fishermen who often face economic challenges due to the fuel costs of conventional engines. Additionally, the use of conventional engines in fishing activities contributes to carbon emissions, which can harm the environment and pose health risks for the fishermen. The Manta One technology innovation at Kelan Beach helps fishermen reduce operating costs and encourages the use of environmentally friendly engines. The implementation of Manta One technology meets the elements and processes of innovation diffusion, proving efficient in its application. However, regarding effectiveness, the implementation of Manta One is still considered suboptimal due to the inability to fully meet the operational needs of fishermen, and the relatively high cost remains a factor that prevents its widespread adoption among small-scale fishermen at Kelan Beach.